Comparison of Percutaneous Kyphoplasty With or Without Posterior Pedicle Screw Fixation on Spinal Sagittal Balance in Elderly Patients With Severe Osteoporotic Vertebral Compression Fracture: A Retrospective Study - Zhou, Quan; Zhang, Junxin; Liu, Hao; He, Wei; Deng, Lei; Zhou, Xinfeng; Yang, Huilin; Liu, Tao (Frontiers in Surgery, 2022)
Objective To compare the effects of percutaneous kyphoplasty (PKP) with or without posterior pedicle screw fixation (PPSF) on spinal sagittal balance in elderly patients with severe osteoporotic vertebral compression fracture (sOVCF). Methods From January 2016 to December 2018, 102 elderly patients with single-level thoracolumbar sOVCF were enrolled. Among them, 78 cases underwent PKP (Group A), and 24 cases underwent PPSF+KP (Group B). Clinical evaluation included perioperative parameters, Oswestry Disability Index (ODI) and Visual Analog Scale (VAS) for back pain; Radiographic evaluation included anterior vertebral height (AVH) and rate (AVHr), local kyphotic angle (LKA), and spino-pelvic sagittal balance parameters. Results Perioperative parameters including operation time, blood loss, fluoroscopic time and hospital stay in Group A were less than those in Group B (p < 0.05). Compared with the pre-operative results, the ODI and VAS scores of both groups decreased significantly in the three follow-ups after surgery (p < 0.05). The post-operative ODI and VAS scores of Group A were significantly better than those of Group B, but the results were opposite at the final follow-up (p < 0.05). Compared with the pre-operative values, except that there was no significant difference in pelvic incidence (PI) (p > 0.05), other radiographic parameters of both groups were improved significantly in the three follow-ups after surgery (p < 0.05). The AVH, AVHr, LKA and lumbar lordosis (LL) in Group B were better than those in Group A in the three follow-ups after surgery (p < 0.05). At the final follow-up, the sacral slope (SS) and pelvic tilt (PT) differed significantly between the two groups (p < 0.05). Conclusions Both PPSF+KP and PKP can achieve favorable clinical outcomes and maintain the spinal sagittal balance. Compared with PPSF+KP, PKP showed more significant advantages in the early post-operative period. However, in the long-term follow-up, PPSF+KP showed better clinical outcomes and may be better than PKP in maintaining spinal sagittal balance.